Statistical methods - Hurtado, Alberto (1945)
The analysis, interpretation and publication of quantitative data and its comparative study with similar data required of Medicine, aligual in other sciences, the use of statistical methods. Some familiarity with these methods, and the terms used, it has become also suitable for those who query the medical literature, or the frequency of inclusion in items of various kinds.